Design and performance verification of a novel vascular anastomosis connector - Fuqiang Lai; Changsheng Cao; Weiqiang Zou; Yumei Li; Wenge Liu; Zhihuang Qiu; Liangwan Chen (Scientific Reports)
Abstract Rapid and safe vascular anastomosis can improve the success rate of surgical procedures and further promote wound healing in patients. Vascular anastomosis connectors (VACs) hold significant potential for facilitating rapid and safe anastomosis. In this study, polylactic acid (PLA) and polycarbonate (PC-ISO) are selected as the materials to prepare VACs. The biomedical properties of the two materials are evaluated, and based on these results, conical thread snap-type VACs are designed. The anastomotic performance of the VACs is assessed using an extracorporeal mock circulation system (MCS). The results show that both PLA and PC-ISO degrade slowly in a simulated body fluid environment, with the sample weight change remaining within 0.37 wt%. Moreover, both materials exhibit good blood compatibility, showing no potential cytotoxicity. In addition, cells adhere well to their surfaces for proliferation, indicating strong biocompatibility. The in vitro MCS simulation tests reveal that both types of VACs can achieve rapid vascular anastomosis, meeting the performance requirements for tensile strength and leak resistance.